Original paperIs there a subset of patients with recurrent cancer in the vagina who are not candidates for interstitial brachytherapy that can be treated with multichannel vaginal brachytherapy using graphic optimization? - Singh, Deepinder P.; Bylund, Kevin C.; Matloubieh, Ahmad; Mazloom, Ali; Gray, Alexander; Sidhu, Ravinder; Barrette, Lucille; Chen, Yuhchyau (Journal of Contemporary Brachytherapy, 2015)
Purpose : To evaluate recurrent vaginal cancer treated with vaginal brachytherapy (VBT) using graphic optimization in patients not amenable to surgery and interstitial brachytherapy (ISBT). Material and methods: We retrospectively reviewed the records of 5 patients with recurrent cancer in the vagina that were deemed not to be good candidates for ISBT implant because of medical reasons. All patients received computed tomography/magnetic resonance imaging (CT/MRI) based evaluation in addition to a detailed clinical examination, and were noted to have recurrent nodules in the vagina with size ranging from 10-25 mm. Four of the 5 patients had recurrent disease in the vaginal apex, whereas one patient had recurrence in the lateral vaginal wall. Subsequently, all patients were treated with external beam radiation therapy (EBRT) followed by multichannel vaginal cylinder (MVC)-based VBT using graphic optimization for shaping the isodose to improve the clinical target volume (CTV) coverage, as well as to spare the organs at risk (OAR). The dose to the bladder and rectum with regard to 0.1 cc, 1 cc, and 2 cc were recorded. Results : Median age of the patients was 78 years (range 58-86 years). Thickness of the lesions before VBT ranged from 6-15 mm. All patients were followed up with MRI at 3 months. All patients but one demonstrated complete clinical/ radiological response of the tumor. No patient had any grade III/IV toxicity at 24 months. Conclusions : MVC-based VBT using graphic optimization is safe and yields favorable results if used judiciously.